Interaction between the aryl hydrocarbon receptor and transforming growth factor-beta signaling pathways: evidence of an asymmetrical relationship in rat granulosa cells - Bussmann, Ursula Agnes (2008)
The aryl hydrocarbon receptor (AHR) mediates toxic responses to environmental contaminants and plays pivotal physiological roles in various biological processes as well, particularly in ovarian function. It is well documented that expression and function of the AHR is negatively regulated by transforming growth factor-beta (TGF-beta) in many cell types. In addition, several studies indicate that AHR activity inhibits TGF-beta expression and function in some systems. However, the interplay between these two signals is highly dependent upon the cell type being studied, precluding a generalization about the outcome of such interaction. Therefore, the goal of the present study was to determine the effect of TGF-beta on AHR expression and activation in granulosa cells, an ovarian cell type where the growth factor is mitogenic and AHR activation has been associated with promotion of proliferation as well. In addition, we conducted experiments aimed at evaluating the effect of AHR ligands on TGF-beta action in our system. Results presented herein demonstrate that AHR expression is not regulated by TGF-beta in rat granulosa cells, neither at the mRNA level nor at the protein level. Moreover, we find that the growth factor does not alter the transcriptional function of the AHR. Conversely, we show that activation of AHR by an agonist deregulates TGF-beta function in granulosa cells, inhibiting its transcriptional activity and its mitogenic action. The described one-sided interplay between TGF-beta and AHR signaling pathway may help provide a mechanistic explanation to some of the physiological outcomes of AHR or TGF-beta activation in granulosa cells.